Pengaruh Gaya Kepemimpinan, Komunikasi, Dan Kerjasama Tim Terhadap Kinerja Karyawan ( Studi Pada PT. Jawara Bangun Persada Karangploso Malang ) - Lia Setyo Rimawati; Abdul Kodir Djaelani; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This research was conducted to determine the effect of leadership style, communication, and teamwork on employee performance at PT. Jawara Builds Persada Karangploso Malang. This research belongs to the type of explanatory research with a quantitative approach, which was conducted to examine the effect between variables. In this study, the sampling technique used was saturated sampling technique because the population in the study was less than 100 people, so the number of samples in this study were all members of the population, amounting to 36 people.To solve the problem in this research, using validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test, classical assumption test. This study uses multiple linear regression analysis with the help of SPSS 25. The results of this study are that there is a simultaneous influence between the variables of Leadership Style, Communication, and Teamwork on Employee Performance in the study at PT Jawara Bangun Persada Karangploso Malang. There is a partial influence between Leadership Style, Communication, and Teamwork on Employee Performance Study at PT. Jawara Bangun Persada Karangploso Malang. Keywords : Leadership Style, Communication, Teamwork, and Employee Performance.